Tingkatkan Kesejahteraan Ibu Melalui Facial Massage Sebagai Upaya Perawatan Prenatal Dan Post Natal Di Kabupaten Bulukumba - Erniawati Erniawati; Sumarni; Husnul Khatimah; Ariani; Sri Ningsih (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Facial Massage has long been known to have significant benefits in improving the well-being of pregnant women. This community service program aims to introduce facial Massage as one of the beneficial prenatal and postnatal care practices for the health of pregnant and postpartum women. Through this program, safe and effective facial Massage techniques are taught to the participants. Additionally, information about the benefits of facial Massage in reducing stress, improving blood circulation, and enhancing sleep, all of which are crucial factors in the well-being of pregnant and postpartum women, is provided. Consequently, it is hoped that this program can positively contribute to improving the well-being of women in the community. The community service activities are implemented in pregnant women residing in Padang Village, Bulukumba Regency. The activities utilize the homecare method for conducting massages on pregnant women. The implementation period is in March 2024. The target participants include 5 pregnant women with gestational ages between 20 to 35 weeks and 5 postpartum women. This activity has an impact on the community, especially pregnant and postpartum women who feel more comfortable after receiving facial Massage therapy for approximately 60 minutes.